Anomalies in T Cell Function Are Associated With Individuals at Risk of Mycobacterium abscessus Complex Infection - Lutzky, Viviana P.; Ratnatunga, Champa N.; Smith, Daniel J.; Kupz, Andreas; Doolan, Denise L.; Reid, David W.; Thomson, Rachel M.; Bell, Scott C.; Miles, John J. (Frontiers in Immunology, 2018)
The increasing global incidence and prevalence of non-tuberculous mycobacterial (NTM) infection is of growing concern. New evidence of person-to-person transmission of multidrug-resistant NTM adds to the global concern. The reason why certain individuals are at risk of NTM infections is unknown. Using high definition flow cytometry we studied the immune profiles of two groups of at risk of Mycobacterium abscessus complex infection and matched controls. The first group were cystic fibrosis (CF) patients and the second group were elderly individuals. CF individuals with active Mycobacterium abscessus complex infection or a history of Mycobacterium abscessus complex infection exhibited a unique surface T cell phenotype with a marked global deficiency in TNFα production during mitogen stimulation. Importantly, immune-based signatures were identified that appeared to predict at baseline the subset of CF individuals who were at risk of Mycobacterium abscessus complex infection. In contrast, elderly individuals with Mycobacterium abscessus complex infection exhibited a separate T cell phenotype underlined by the presence of exhaustion markers and dysregulation in type 1 cytokine release during mitogen stimulation. Collectively, these data suggest an association between T cell signatures and individuals at risk of Mycobacterium abscessus complex infection, however validation of these immune anomalies as robust biomarkers will require analysis on larger patient cohorts.